2015
DOI: 10.1177/0886260515609583
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Aggression Victimization and Perpetration Among Female and Male University Students in Poland

Abstract: This study examined the prevalence of victimization and perpetration of sexual aggression since age 15 in a convenience sample of 565 Polish university students (356 females). The prevalence of sexual aggression was investigated for both males and females from the perspectives of both victims and perpetrators in relation to three coercive strategies, three different victim-perpetrator relationships, and four types of sexual acts. We also examined the extent to which alcohol was consumed in the context of sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
5
23
0
1
Order By: Relevance
“…However, the findings are consistent with several recent studies from the cross-cultural literature that also found no or only few gender differences (e.g., Brazil: D'Abreu et al, 2013; U.S.: Hines et al, 2012; Turkey: Schuster et al, 2016; Poland: Tomaszewska and Krahé, 2015) or even higher victimization rates among men compared to women (Krahé et al, 2015), challenging traditional views and stereotypes about sexual aggression victimization. More research is needed to understand social processes, cultural variables, sexuality related cognitions (e.g., sexual scripts, sexual self-esteem) as well as risky sexual behavior which may explain the absence of gender differences in victimization, particularly in the non-Western countries.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the findings are consistent with several recent studies from the cross-cultural literature that also found no or only few gender differences (e.g., Brazil: D'Abreu et al, 2013; U.S.: Hines et al, 2012; Turkey: Schuster et al, 2016; Poland: Tomaszewska and Krahé, 2015) or even higher victimization rates among men compared to women (Krahé et al, 2015), challenging traditional views and stereotypes about sexual aggression victimization. More research is needed to understand social processes, cultural variables, sexuality related cognitions (e.g., sexual scripts, sexual self-esteem) as well as risky sexual behavior which may explain the absence of gender differences in victimization, particularly in the non-Western countries.…”
Section: Discussionsupporting
confidence: 91%
“…With respect to victim-perpetrator relationship constellations, sexual aggression victimization and perpetration were more common between (ex-)partners and friends/acquaintances than between strangers, which was in line with Hypothesis 3 and past national and international evidence (e.g., Lehrer et al, 2013a; Tomaszewska and Krahé, 2015; Schuster et al, 2016). This indicates that sexual aggression is more prevalent among persons who know each other than between unknown parties, disconfirming stereotyped views on sexual aggression.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These cases have often been excluded from consideration altogether (see, e.g., Anderson & Aymami, 1993), but where they have been considered it has either been alongside an exploration of a range of other non-consensual sexual acts perpetrated by women (see, e.g., Struckman-Johnson & Struckman-Johnson, 1998), in the context of a comparative approach also looking at forced sex experiences of women (Struckman-Johnson, 1988), or in some cases, combinations of the above (see, e.g., Tomaszewska & Krahé, 2018). As such, it is almost impossible to paint any sort of accurate picture around sexually aggressive strategies used by women specifically in FTP cases.…”
Section: Introductionmentioning
confidence: 99%
“…IPV is increasingly becoming a public health problem among young persons and male and female university students [9][10][11] . Among university students in high income countries, e.g., in Finnland 42.0% reported physical violence 12 in Poland 34.3% of females and 28.4% of males reported sexual aggression victimization 13 and in Spain 15.2% of females reported lifetime genderbased violence victimization 14 . Among university students in low-and middle-income countries, e.g., in Chile 31% of women and 21 % of men reported exposure to sexual violence 15 in China the rates of being the victim of physical assault and sexual coercion were 18.0% and 5.1%, respectively 16 in Nigeria (females) 44.1% reported life-time prevalence of IPV 17 46.7% sexual violence 18 and 22.8% and 22.2% of students experienced physical and sexual violence, respectively 19 in Russia 25.5% were the victims of physical partner violence and 24.1% were sexually coerced in the previous year 20 and in Uganda 10%, with no significant gender differences, had exposure to physical partner violence 9 .…”
Section: African Journal Of Reproductive Health March 2016; 20 (1): 30mentioning
confidence: 99%